Breakfast Habits Relationship With Blood Sugar Levels And School Performance In Healthy Children In Yayasan Bali Kuna Santi, Karangasem, Bali - Sidiartha, I Gusti Ayu Diah Febriyani; Indriyani, Desak Putu Rendang; Natalia, Vica; Fenia, Irene; Gozali, Ferry Suganda (Sean Institute, 2024)
Background: These days, an increasing number of young people skip breakfast for a variety of reasons. Skipping breakfast is a behavior that raises the risk of metabolic disorders such as diabetes and cardiovascular disease, decreased sleep quality, as well as reduced concentration and creativity. This behavior is said to be increased glycemic responses that associated with increased blood sugar levels. Skipping breakfast also associated with decreased of concentration, creativity, and school performance. This research was conducted to examine whether there is a significant relationship between breakfast habits and blood sugar levels as well as school performance in healthy children. Methods: A cross-sectional design with 43 healthy children aged 8 months to 15 years as research participants. Participants were assessed for weight, height, body mass index (BMI), breakfast habits, school performance, and blood sugar levels. The SPSS software’s One-Way ANOVA test were used to examine the exam outcomes. Results: A One-Way ANOVA analysis produced p value of 0.353 (>0.05) for blood sugar levels and p value of 0.003 (<0.05) for school performance. Conclusion: While there is no statistically significant relationship between breakfast habits and blood sugar levels in healthy children, there is statistically significant relationship between breakfast habits and school performance. These results may be attributed to several factors that can be considered for further research.